Health Insurance : Use of Health Care Services by the Poor - Efficiency and Equity Issues in the Province of Kon Tum - Castel, Paulette (World Bank, Washington, DC, 2017)
The study merged two databases: the database on patients' visits collected for claim control and reimbursement purpose and, the database on the insured that is used to issue the health insurance cards. This study investigated these issues through the analysis of individual's health insurance data of the Provincial Social Security (PSS) heath insurance of Kon Tum. One of the important political goals in the coming years is the achievement of universal coverage of health insurance. For that purpose the government is pursuing the strategy (started in 2005) to provide free health insurance cards to all the poor, the ethnic minority populations and the persons living in remote or mountainous areas. One of the important political goals in the coming years is the achievement of universal coverage of health insurance. For that purpose the government is pursuing the strategy (started in 2005) to provide free health insurance cards to all the poor, the ethnic minority populations and the persons living in remote or mountainous areas.